Teratogenic impacts of Antiepileptic drugs on development, behavior and reproduction in Drosophila melanogaster. - R, S.; K, N. (Neurotoxicology and teratology, 2023)
Clobazam (CLB) and Vigabatrin (VGB) are the two widely used Antiepileptic drugs, which may have teratogenic potentiality and it has been evaluated in the fruit fly Drosophila melanogaster. These different concentrations of CLB (0.156, 0.25, and 0.312 ?g/ml) and VGB (17.6, 22, and 44 ?g/ml) were used to evaluate the life-history parameters, developmental, and behavioral abnormalities. The results revealed that life-history parameters (fecundity, fertility, larval and pupal mortality) were significantly affected along with varied developmental duration, and pupal and adult deformities in flies on exposure of CLB and VGB in concentration dependent manner. The present study demonstrated that the prenatal treatment of CLB and VGB has displayed clear teratogenic potentiality with various deformities in the fruit fly. The findings could be correlated with the various abnormalities in human caused by the use of AEDs.